The house of rothschild volume 2: the world's banker: 1849-1999 - Ferguson, Niall (New York Penguin, 2014)
Niall Ferguson's House of Rothschild: Money's Prophets 1798-1848 was hailed as a 'great biography' by Time magazine and named one of the best books of 1998 by Business Week.
Includes index
Keywords: Biography